Flexible graphite films with high conductivity for radio-frequency antennas. (April 2018) - Song, Rongguo; Wang, Qianlong; Mao, Boyang; Wang, Zhe; Tang, Danli; Zhang, Bin; Zhang, Jingwei; Liu, Chengguo; He, Daping; Wu, Zhi; Mu, Shichun
Abstract: The low conductivity and fragile mechanical toughness of conventional carbon material based films are major barriers for their applications in modern electronics, especially in flexible radio frequency electronics, such as antennas. In order to optimize their performance, the electrical and mechanical properties of the materials need to be improved. In this work, flexible graphite films, fabricated by high temperature thermal treatment of polymer precursor and subsequence compression rolling, are designed and explored to create dipole antennas for radio frequency applications. It is shown that the flexible graphite films with 808.8 cm 2 /V·sec carrier concentration have a high conductivity of 1.1 × 10 6 S/m. We demonstrate that the resulting flexible graphite film dipole antennas can not only produce a relatively high peak gain of 1.45 dB with comparable return loss, bandwidth, and radiation patterns to an identical copper antenna, but also have excellent structure stability and mechanical flexibility. Moreover, the density of the graphite film is 5 times less than the copper film. This indicates that the tailored flexible graphite film could be a new alternative way to produce superb flexible and efficient radio-frequency antennas. Graphical abstract: Image 1